Biomechanical analysis of loaded plyometric exercises - Gold, M. E.; Frisk, H. L.; Biggs, B. R.; Blankenship, M. J.; Ebben, W. P. (ISBS Proceedings Archive (Michigan), 2021)
Plyometric intensity and specificity are determined by the exercises performed. This study assessed ground reaction forces (GRF) in the frontal (F), horizontal-anterior (H), and vertical (V) planes, and the ratio of H to V GRF (H:V) of plyometric exercises and load conditions. Subjects (N=15) performed five plyometric variations with five handheld loads on two force platforms. A two-way RM ANOVA was used. Analysis of F GRF revealed main effects for plyometric exercise (p = 0.004). Analysis of H GRF revealed main effects for plyometric load (p = .042) and plyometric exercise (p = 0.001). Analysis of V GRF revealed main effects for plyometric load (p = 0.001) and plyometric exercise (p = 0.001). Analysis of H:V revealed main effects for plyometric exercise (p = 0.001). Practitioners should use the plyometric exercises and loads that optimize the kinetics and transfer of training.